Soldier girls : the battles of three women at home and at war - Thorpe, Helen, 1963- (Scribner, 2014)
Describes the experiences of three women soldiers deployed to Afghanistan and Iraq to reveal how their military service has affected their friendship, personal lives and families, detailing the realities of their work on bases and in war zones and how their choices and losses shaped their perspectives.